LEXICAL ERRORS IN THE ACQUISITION OF THE LATVIAN LANGUAGE AS THE SECOND LANGUAGE AT PRESCHOOL AGE - Tomme-Jukēvica, Ingēra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The lexical component plays a significant role in the first stages of language acquisition. However, there has been relatively little research into the lexical errors of young second language learners at preschool age. Moreover, the Russophone children’s Latvian language as a second language has not been analyzed in lexical aspect so far. The aim of this study is to investigate types of lexical errors and the reasons for their occurrence. The data on 12 six-seven year old children, who study L2 (Latvian) in a formal language learning context were collected. Children’s speech (using the author’s compiled vocabulary test for identification of productive skills of single-word vocabulary) was recorded on a dictaphone. Errors were identified, classified and tabulated. The findings illustrate three categories of lexical errors: interlingual (L1-transfer), intralingual (L2-influence) and mutual (both L1- and L2-influence) in the oral presentations of the participants. Semantic, morphological, and phonological types of errors featuring in them were identified. The results imply that children (like adults) learning L2 vocabulary use the strategy of LI (Russian) lexical transfer (e. g., borrowing, coinage) to cope with the lexical difficulties imposed by the new vocabulary. Determination of the particular lexical errors, and establishment of the causes that generate them will help the teacher delimitate their approach to Latvian vocabulary teaching. To prevent children’s errors some recommendations are proposed. It is advisable to devise and incorporate special exercises and activities directed to the practice of problematic lexical areas.